Workload realignment in line with migration of process in finance and accounting operations in a business service center - Lasala, Rojean Carlo C. (Animo Repository, 2021)
This action research addresses the operational and human resource deficiencies and issues that were encountered in a specific team from a huge business service center providing finance and accounting operations for a hospital industry in the United States. The situation was aggravated by the non-alignment of tasks in the migrated processes from the U.S. counterparts to the business service center staff. Because of these, the team cannot achieve the Service Level Agreement (SLA) targets and continuously encounter escalation from the stakeholders. The action researcher collaborated with the peers in conducting two action research cycles. First, the team used Relational and Contractual Governance of Process Standardization to BPO Success Framework to effectively address the problem. Another framework used during the second cycle was the DMAIC framework to further improve and address the gaps during the first cycle. After the two action research cycles, the results demonstrated that having an alignment of the business service center staff’s scope of work according to their appropriate job levels was indeed helpful in improving the team’s performance, achieving SLA targets and stakeholder’s expectations.